Do cognitive tasks during gait increase the risk of accidents with pedestrians? A study based on electromyographic parameters - Hallal, Camilla Zamfolini (2017)
AbstractIntroduction Accidents involving pedestrians are responsible for many cases of serious injuries and deaths. Crossing streets safely requires complex planning and cognitive demand because it is necessary to perform more than one task at a time.Objective The aim of this study was to identify electromyographic changes during gait in young subjects who performed the cognitive tasks concurrently.Methods The study included 17 younger women aged between 18 and 25 years. Data collection was performed on a treadmill. The volunteers were instructed to walk in four different conditions: normal gait (NG), gait with dual easy task (DET), gait with dual hard task (DHT) and gait with dual mixed task (DMT).Results Significant differences were found between the MN condition to the other conditions for all muscles and, during the NG, smaller values of muscle activation were found. Muscle co-contraction between muscles VM / BF showed a significant difference between the conditions of NG and DMT (p = 0.04) and, during the NG, smaller values of co-contraction were observed.Conclusion The data of this study permits to conclude that the competition between motor and cognitive resources significantly affects the levels of muscle activation and co-contraction during gait in young adult women. Thus, we conclude that the performance of dual cognitive tasks while driving can be considered a risk factor for safe driving.